Diversificando o ensino de matemática com ênfase na resolução de problemas - Aguiar, Paulo Célio (2016)
This study begins with a brief account of my professional experience and a remark made to appropriate the statistical data of a state school, which I linked meeting. It has been found that it has a considerable rate of failure in Mathematics, and a regular performance in this discipline in external evaluations. In an attempt to identify the causes, was made an observation of lessons, interviews with students and teachers, where we realized that fit present a proposal to diversify the teaching of this discipline in order to improve student learning and hence their performance in evaluations. This discussion extends in the second chapter, which briefly questioned is the way this course has been taught in most schools. É also presented an account of a successful experience. In the third chapter, based on my vision teacher and former manager, I present an educational proposal emphasizing motivation and diversification. From the fourth chapter, problem solving takes the role of main theme of this dissertation and is seen on various aspects. First, we used the mathematics of history to understand the degree of interest of the ancient mathematicians in this theme. In then it is treated as a teaching strategy for teaching mathematics. In the final chapter, we present a series of problems solved, well chosen criterion, which explores various techniques and solving strategies. We ended by suggesting to readers, a list of problems containing some tips and answers.